On stability and boundedness of solutions of a certain fourth-order delay differential equation - Emmanuel O. Okoronkwo (International Journal of Mathematics and Mathematical Sciences)
Using a Razumikhin - type theorem, we deduce sufficient conditions that guarantee the uniform asymptotic stability and boundedness of solutions of a scalar real fourth-order delay differential equation. The Lyapunov function constructed for an ordinary fourth-order differential equation is seen to work for the delay system.